Wood functional anatomy of Chiococca alba Hitch. (Rubiaceae) from cerrado - João Carlos Ferreira de Melo Júnior; Maick William Amorim; Gustavo Borda de Oliveira; Celso Voos Vieira (Acta Biológica Catarinense, 2017)
The wood anatomy is able to evidence systematic and ecological aspects associated with the evolution and functionality of the secondary xylem. The present study was carried out using wood of Chiococca alba (Rubiaceae) from cerrado (savannah), to describe its anatomy and to verify if the hydraulic architecture of this species corroborates the theory that postulates the functional tendency that optimizes the transport efficiency associated with safety. The anatomical analysis followed the conventional protocols of wood anatomy. Different indexes of wood hydraulics quantification were calculated, such as solitary vessels index, vessel grouping, conductivity, vessel collapse, theoretical resistance to vessel implosion and mesomorphism. The structural characteristics described for C. alba are in agreement with the general anatomical descriptions for the Rubiaceae family that relate the presence of exclusively solitary vessels and small diameter, simple perforation plates, alternate intervessel pits, apotracheal parenchyma in species with non-septate fibers and narrow and heterogeneous rays. The calculated indexes showed that C. alba is a xerophyte species with great resistance to the collapse of the vessels during the transport of water, little vulnerability to embolism and relative efficiency in the transport when compared to other species of its subfamily (Cinchonoideae) in function of the typical low water availability of the savannah soil.